Penyesuaian Lapisan dan Tarif PPh Orang Pribadi: Agresif atau Progresif? - Kalyana Mitta Kristanti (Owner : Riset dan Jurnal Akuntansi, 2022)
In 2022, Indonesia would apply changes in tax brackets and rates for personal income tax. This adjustment is based on the Article 17 Paragraph 1 Tax Harmonization Law Number 7 of 2021. The government tries to accommodate the needs of the community through formulating process of this regulation. In particular, it provides convenience to the lower-middle income community and encourages an even distribution of income. People belonging to the high wealth income will be subject to the highest tariffs that have just been set through this law. Through a qualitative descriptive method in which data collection is carried out by taking from literature review; law, articles, books, and website, the author tries to analyze changes in brackets and rates of personal income tax. This study presents illustrations of the calculation to explain the difference in the amount of income tax payable before and after the implementation of the Tax Harmonization Law. In addition, the analysis of the principles of equity and democracy on the adjustment of layers and tax rates is elaborated in this paper. The results obtained explain that with the application of the new tax rate, taxpayers get a tax burden relief because the tax expense is lower due to the broadening of income range. However, wealthy taxpayers will pay more taxes because of the higher tax rates. This condition proves that the new tax rate supports vertical fairness in the taxation system. In addition, the implementation of regulations related to tax rates adjustment provides evidence that the implementation of democracy has been implemented. The adjustment of tax brackets and rates has a positive impact on the community and the government so that the allocation of tax revenues can run optimally to support the welfare of the community.